Modified rice bran arabinoxylan as a nutraceutical in health and disease-A scoping review with bibliometric analysis. - Soo Liang Ooi; Peter S Micalos; Sok Cheon Pak (PLoS ONE)
Rice bran arabinoxylan compound (RBAC) is a polysaccharide modified by Lentinus edodes mycelial enzyme widely used as a nutraceutical. To explore translational research on RBAC, a scoping review was conducted to synthesise research evidence from English (MEDLINE, ProQuest, CENTRAL, Emcare, CINAHL+, Web of Science), Japanese (CiNii, J-Stage), Korean (KCI, RISS, ScienceON), and Chinese (CNKI, Wanfang) sources while combining bibliometrics and network analyses for data visualisation. Searches were conducted between September and October 2022. Ninety-eight articles on RBAC and the biological activities related to human health or disease were included. Research progressed with linear growth (median = 3/year) from 1998 to 2022, predominantly on Biobran MGN-3 (86.73%) and contributed by 289 authors from 100 institutions across 18 countries. Clinical studies constitute 61.1% of recent articles (2018 to 2022). Over 50% of the research was from the USA (29/98, 29.59%) and Japan (22/98, 22.45%). A shifting focus from immuno-cellular activities to human translations over the years was shown via keyword visualisation. Beneficial effects of RBAC include immunomodulation, synergistic anticancer properties, hepatoprotection, antiinflammation, and antioxidation. As an oral supplement taken as an adjuvant during chemoradiotherapy, cancer patients reported reduced side effects and improved quality of life in human studies, indicating RBAC's impact on the psycho-neuro-immune axis. RBAC has been studied in 17 conditions, including cancer, liver diseases, HIV, allergy, chronic fatigue, gastroenteritis, cold/flu, diabetes, and in healthy participants. Further translational research on the impact on patient and community health is required for the evidence-informed use of RBAC in health and disease.